ANALISIS KEBUTUHAN PESERTA DIDIK TERHADAP PERMAINAN ROUND OF DRAGON SNAKE RAINBOW SEBAGAI MEDIA LAYANAN BIMBINGAN KONSELING - Noor Halisa Anhar; Sulistiyana Sulistiyana; Nina Permata Sari (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Education in the globalization era demands mastery of social-emotional intelligence, but traditional counseling methods are often considered less appealing by Generation Z, who are accustomed to interactive technology. This study focuses on analyzing students' needs for the Round of Dragon Snake Rainbow game as an innovative medium for guidance and counseling services. Using a descriptive quantitative approach, this study involved forty-five eighth-grade students at SMP Negeri Tujuh Belas Banjarmasin through a purposive sampling technique. The systematic research stages included distributing digital-based questionnaires that measured social-emotional aspects, observations, values, and social responsibility, then analyzed using descriptive statistics. The research findings revealed that the majority of respondents needed this media with an average score of 135.33. Quantitatively, 60 percent of students were in the high-needs category, while 22 percent were in the medium category, and the remaining 18 percent were in the low category. Analysis per dimension showed that the most dominant needs were in the value aspect at 60 percent and the observation aspect at 56 percent. The main conclusion confirms that the Round of Dragon Snake Rainbow game is urgently needed to be implemented as an interactive, fun, and relevant counseling service for adolescents. This media has been proven to facilitate active student involvement while supporting holistic character development through direct learning experiences that are very meaningful for all students.